2021
DOI: 10.3390/biomedicines9030230
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Inflammatory Extracellular Vesicles in Plasma and Cerebrospinal Fluid: An Optimized Diagnostic Model for Parkinson’s Disease

Abstract: Extracellular vesicles (EVs) play a central role in intercellular communication, which is relevant for inflammatory and immune processes implicated in neurodegenerative disorders, such as Parkinson’s Disease (PD). We characterized and compared distinctive cerebrospinal fluid (CSF)-derived EVs in PD and atypical parkinsonisms (AP), aiming to integrate a diagnostic model based on immune profiling of plasma-derived EVs via artificial intelligence. Plasma- and CSF-derived EVs were isolated from patients with PD, m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…[ 5 ] We took advantage from reproducible flow cytometer assay that has been previously standardized and validated for the detection and characterization of EV surface signatures. [ [16] , [17] , [18] , [19] ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] We took advantage from reproducible flow cytometer assay that has been previously standardized and validated for the detection and characterization of EV surface signatures. [ [16] , [17] , [18] , [19] ]…”
Section: Introductionmentioning
confidence: 99%
“…Since 2018, this assay has been used for surface protein profiling of EVs from various body fluids, i.e. blood plasma 19,[37][38][39][40][41] , serum 19,[42][43][44] , urine 44 , cerebral spinal fluid 38 and lymphatic drain fluid 45 of healthy subjects and patients, using a wide variety of EV enrichment/purification protocols, EV quantification methods and input EV amounts. To our knowledge no studies have been reported on the use of this assay on EVs purified from different body fluids collected on the same day from the same donor, isolated by similar protocols and analysed by pan-tetraspanin as well as single tetrapsanin detection.…”
Section: Discussionmentioning
confidence: 99%
“…The primary limitation of this study is that the number of patients is low, which could compromise the validity of our diagnostic model. However, recently, several robust studies constructed the diagnostic model, based on a comparable size of subjects [ 49 , 50 , 51 ]. In terms of the advanced age in CRC patients, compared to healthy controls, it is difficult to completely eradicate the potential age-related bias in immune cells.…”
Section: Discussionmentioning
confidence: 99%